2017
DOI: 10.1021/acs.jpcc.7b07299
|View full text |Cite
|
Sign up to set email alerts
|

Radiolytic Dissolution of Calcite under Gamma and Helium Ion Irradiation

Abstract: Samples of calcite have been irradiated using both the 60.7 MeV helium ion beam of the ARRONAX (Nantes, France) cyclotron and 661.7 keV gamma radiations. The irradiation of calcite pellets results mainly in radiolytically generated gas (H2, CO2). The presence of superficial water during the calcite irradiation in a humid atmosphere is a key factor for the production of radiolysis gases. Besides, the irradiation of calcite–water biphasic media was performed. The gas released after these irradiations is quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…The radiation chemical behavior of formate has already been the subject of several studies (Albarrán et al 1987, Cai et al 2001, Costagliola et al 2017, Draganić et al 1991. The main formate (or formic acid) degradation reaction by water radiolysis products are the following:…”
Section: Carbonate Radiolysis and Recombination Of Radical Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiation chemical behavior of formate has already been the subject of several studies (Albarrán et al 1987, Cai et al 2001, Costagliola et al 2017, Draganić et al 1991. The main formate (or formic acid) degradation reaction by water radiolysis products are the following:…”
Section: Carbonate Radiolysis and Recombination Of Radical Speciesmentioning
confidence: 99%
“…Recently, we have discussed the impact of ionizing radiations (α-beam and γ-Ray) on calcite and calcium carbonate solutions (Costagliola et al 2017). We have shown that calcite dissolution is accompanied by organic anions formation such as formate, acetate and oxalate ions.…”
Section: Carbonate Radiolysis and Recombination Of Radical Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly notable is the work carried out by Huber and Wächtershäuser [60], showing that several iron sulfur minerals are able to spontaneously catalyze carbon fixation reactions, producing prebiotic molecules. Non-metals may also drive production of simple organic molecules as recent studies of radiolysis reactions driven by U, Th and K decay demonstrate production of simple organic acids such as acetate, formate and oxalate in addition to the more well known H 2 production [22,61]. It is believed that the earliest forms of proto-life may have had metabolisms catalyzed by environmentally available metal-bearing nanominerals [8].…”
Section: Metal Catalysismentioning
confidence: 99%
“…Radiolytic yields in pure water are well constrained 5 , 6 and some monominerals (pyrite, various oxides, mordenite, calcite) are known to amplify water-radiolytic H 2 yields when irradiated by γ rays 7 9 . Similarly, other oxides and calcite enhance water-radiolytic H 2 production following exposure to α particles 9 11 . The effect of mineralogically complex natural materials on H 2 yields is previously unexplored.…”
Section: Introductionmentioning
confidence: 99%